Critical Infrastructure Protection VI 6th IFIP WG 11.10 International Conference, ICCIP 2012, Washington, DC, USA, March 19-21, 2012, Revised Selected Papers - Butts, Jonathan; Shenoi, Sujeet; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The information infrastructure - comprising computers, embedded devices, networks and software systems - is vital to day-to-day operations in every sector: information and telecommunications, banking and finance, energy, chemicals and hazardous materials, agriculture, food, water, public health, emergency services, transportation, postal and shipping, government and defense. Global business and industry, governments, indeed society itself, cannot function effectively if major components of the critical information infrastructure are degraded, disabled or destroyed. Critical Infrastructure Protection VI describes original research results and innovative applications in the interdisciplinary field of critical infrastructure protection. Also, it highlights the importance of weaving science, technology and policy in crafting sophisticated, yet practical, solutions that will help secure information, computer and network assets in the various critical infrastructure sectors. Areas of coverage includes: Themes and Issues; Control Systems Security; Infrastructure Security; and Infrastructure Modeling and Simulation. This book is the sixth volume in the annual series produced by the International Federation for Information Processing (IFIP) Working Group 11.10 on Critical Infrastructure Protection, an international community of scientists, engineers, practitioners and policy makers dedicated to advancing research, development and implementation efforts focused on infrastructure protection. The book contains a selection of sixteen edited papers from the Sixth Annual IFIP WG 11.10 International Conference on Critical Infrastructure Protection, held at the National Defense University, Washington, DC, USA in the spring of 2011. Critical Infrastructure Protection VI is an important resource for researchers, faculty members and graduate students, as well as for policy makers, practitioners and other individuals with interests in homeland security. Jonathan Butts is an Assistant Professor of Computer Science at the Air Force Institute of Technology, Wright-Patterson Air Force Base, Ohio, USA. Sujeet Shenoi is the F.P. Walter Professor of Computer Science and a Professor of Chemical Engineering at the University of Tulsa, Tulsa, Oklahoma, USA.
The European Perspective of Telecommunications as a Critical Infrastructure -- Implementing Critical Information Infrastructure Protection Structures in Developing Countries -- Integrity-Organization Based Access Control for Critical Infrastructure Systems -- Analysis of Field Devices Used in Industrial Control Systems -- A Firmware Verification Tool for Programmable Logic Controllers -- Quantifying Controller Resilience Using Behavior Characterization -- Using Bloom Filters to Ensure Access Control and Authentication Requirements for SCADA Field Devices -- Agent Interaction and State Determination in SCADA Systems -- Infrastructure Protection in the Dutch Financial Sector -- Privacy-Preserving Power Usage Control in the Smart Grid -- Effects of Time Delays in the Electric Power Grid -- Measuring Name System Health -- Emergency Messages in the Commercial Mobile Alert System -- A One-Dimensional Sparse Space-Time Specification of the Generalized Railroad Crossing -- A Networked Evidence Theory Framework for Critical Infrastructure Modeling -- Enabling the Exploration of Operating Procedures in Critical Infrastructures.
Keywords: Computer science; Data protection; Information storage and retrieval systems; Computer simulation; Computers -- Law and legislation; Information Systems; Computer Science; Systems and Data Security; Management of Computing and Information Systems; Legal Aspects of Computing; Computers and Society; Simulation and Modeling; Information Storage and Retrieval